Phylogeography of the walnut twig beetle, Pityophthorus juglandis, the vector of thousand cankers disease in North American walnut trees. - Paul F Rugman-Jones; Steven J Seybold; Andrew D Graves; Richard Stouthamer (PLoS ONE)
Thousand cankers disease (TCD) of walnut trees (Juglans spp.) results from aggressive feeding in the phloem by the walnut twig beetle (WTB), Pityophthorus juglandis, accompanied by inoculation of its galleries with a pathogenic fungus, Geosmithia morbida. In 1960, WTB was only known from four U.S. counties (in Arizona, California, and New Mexico), but the species has now (2014) invaded over 115 counties, representing much of the western USA, and at least six states in the eastern USA. The eastern expansion places TCD in direct proximity to highly valuable (> $500 billion) native timber stands of eastern black walnut, Juglans nigra. Using mitochondrial DNA sequences, from nearly 1100 individuals, we examined variation among 77 samples of WTB populations across its extended range in the USA, revealing high levels of polymorphism and evidence of two divergent lineages. The highest level of genetic diversity for the different lineages was found in the neighboring Madrean Sky Island and Western New Mexico regions, respectively. Despite their proximity, there was little evidence of mixing between these regions, with only a single migrant detected among 179 beetles tested. Indeed, geographic overlap of the two lineages was only common in parts of Colorado and Utah. Just two haplotypes, from the same lineage, predominated over the vast majority of the recently expanded range. Tests for Wolbachia proved negative suggesting it plays no role in "driving" the spread of particular haplotypes, or in maintaining deep levels of intraspecific divergence in WTB. Genotyping of ribosomal RNA corroborated the mitochondrial lineages, but also revealed evidence of hybridization between them. Hybridization was particularly prevalent in the sympatric areas, also apparent in all invaded areas, but absent from the most haplotype-rich area of each mitochondrial lineage. Hypotheses about the specific status of WTB, its recent expansion, and potential evolutionary origins of TCD are discussed.